Generation of Trichoderma reesei Mutant with Enhanced Xylanase Activity by Using Disparity Mutagenesis - Watanabe, Taisuke; Nasukawa, Masashi; Yoshida, Yuki; Kogo, Takashi; Ogihara, Jun; Kasumi, Takafumi (Journal of applied glycoscience : JAG, 2019)
In the current study, we attempted to enhance the xylanase activity of Trichoderma reesei ATCC66589 by using disparity mutagenesis, wherein a plasmid harboring proofreading-impaired DNA polymerase δ was inserted. Following selection on xylan-rich media and successive plasmid curing, a mutant showing conidiospores strikingly different from those of the parent strain, with many small humped-surface spheres, was generated. Xylanase and β-xylosidase activities of the mutant XM1, cultivated in xylan medium, were 15.8- and 11.0-fold higher than those of the parent strain, respectively. Furthermore, xylanase activity was generated approximately 24 h in advance compared to that in the parent. In contrast, when cultivated in Avicel medium, its xylanase and β-xylosidase activities were 0.14- and 0.33-fold, respectively, compared to those in the parent. Among the xylan component sugars and related polyols, D-xylose and xylobiose exerted a distinct inductive effect on the xylanase activity in Avicel media, while xylitol and L-arabinose did not. Mutagenesis involved in xylose catabolism is suggestive of changes at the gene transcription level. Although the induction mechanism remains unclear in details, disparity mutagenesis may be useful for obtaining T. reesei mutants with high xylanase activity.